Evaluation of Stability of Cefamandol and Ceftazidime with Clavulanic Acid Against Extended Spectrum ?- Lactamase - Siham S. Shaokat; Hamoudi A. Hameed (College of Pharmacy University of Baghdad, 2017)
The aim of this study is to evaluate in-vitro activity of Cefamandol (Cfm) and Ceftazidime (Cfz), in combination with Clavulanic acid (CA) against ten complicated multiresistant uropathogenic E.coli .One hundred clinical strains were isolated from patients with chronic urinary tract infections (UTIs), these isolates were identified by the Api identification systems. The antimicrobial susceptibility tests were determined by Kirby-Bauer method, all of them were sensitive to Imipenem (Imp). Ten strains were chosen for the present study, they were resistant to Ampicillin (Amp), Amoxicillin (Amo), Carbenicillin (Cb), Ticarcillin (Tic), Azlocillin (Azl), Amoxicillin\ Potassium Clavulanate {Augmentin(Amc)}, (Amo\CA), Ticarcillin\ Potassium Clavulanate Timentin (Tic\CA) ,Cefazolin (Cfo) ,Cefaloridin (Cfr), Cefamandol, (Cfm),Cefoxitin, Ceftazidime (Cfz), Cefixime (Cxm), Cefoperazone( Cfp) and Aztreonam (Atm), also resistant to other antibiotics, Tetracycline(Tc),Cloramphenicol(Cm),Gentamycin(G),Amikacin (Amk), Ciprofloxacin (Cip) and Trimethoprim. 50% of the isolates were resistant to Nalidixic acid and Rifampicin. The minimum inhibitory concentrations of Cefamandol and Ceftazidime were determined, by tube method. Transfer of plasmids were done by direct conjugation test to sensitive standard E.coli ,cell free Î²- lactamases were prepared and detected by macro-iodometric method. The activity of each cell free ÃŸâ€" lactamases extract against Cfm and Cfz were determined by disks diffusion method (microbiological Masuda method). Excellent activities were obtained against these strains when Cfm and Cfz, combined with CA, therefore complete zones of inhibition were obtained indicated the prevalence of extended spectrum Î²- lactamases in E.coli. The stability of Cfm and Cfz in the presence of CA were useful in the treatment of chronic urinary tract infections caused by multiresistant Î²- lactamase (ESBL) producer E.coli. Key words: Extended spectrum Î²- lactamases, Imipenem, Aztreonam, Ceftazidime.